Mitigating jaw osteonecrosis: bioactive glass and pericardial membrane combination in a rat model - Pellicano, Alexandre Antonio; Benites, Bernar M.; Paschoa, Amanda F. N.; Oliveira, Laura C.; Campos, Ana Carolina P.; Martins, Daniel O.; Real, Caroline C.; de Paula Faria, Daniele; Fonseca, Felipe P.; Martinez, Raquel R. C.; Pagano, Rosana L.; Fregnani, Eduardo R. (Frontiers in Oncology, 2024)
Objectives Bisphosphonates (BFs) show clinical effectiveness in managing osteoporosis and bone metastases but pose risks of bisphosphonate-related jaw osteonecrosis (BRONJ). With no established gold standard for BRONJ treatment, our focus is on symptom severity reduction. We aimed to assess the preventive effects of bioactive glass and/or pericardial membrane in a preclinical BRONJ model, evaluating their potential to prevent osteonecrosis and bone loss post-tooth extractions in zoledronic acid (ZA)-treated animals. Methods Rats, receiving ZA or saline biweekly for four weeks, underwent 1st and 2nd lower left molar extractions. Pericardial membrane alone or with F18 bioglass was applied post-extractions. Microarchitecture analysis and bone loss assessment utilized computerized microtomography (CT) and positron emission tomography (PET) with 18F-FDG and 18F-NaF tracers. Histological analysis evaluated bone injury. Results Exclusive alveolar bone loss occurred post-extraction in the continuous ZA group, inducing osteonecrosis, osteolysis, osteomyelitis, and abscess formation. Concurrent pericardial membrane with F18 bioglass application prevented these outcomes. Baseline PET/CT scans showed no discernible uptake differences, but post-extraction 18F-FDG tracer imaging revealed heightened glucose metabolism at the extraction site in the ZA-treated group with membrane, contrasting the control group. Conclusion These findings suggest pericardial membrane with F18 bioglass effectively prevents BRONJ in the preclinical model.